SIMULATION OF ADSORPTION COOLING SYSTEM DRIVEN BY WASTE HEAT FROM ENGINE - KAMARUZAMAN, NURUL AFIQAH (IRC, 2017)
Adsorption cooling system driven by waste heat from car radiator engine is among the alternatives to the conventional automobile air conditioning that has been considered in term of energy savings and environmental issues. The project aims to perform the feasibility study of the proposed adsorption cooling system to be further developed for the application in automotive industry. The timeline proposed to conduct the study is 28 weeks. The model is developed through the set of governing equations. The relations between inlet temperature of hot water to heat the bed, time cycle of adsorption/desorption process, cooling water temperature and chill water temperature with the coefficient of performance (COP) and specific cooling capacity (SCC) is studied. Heating and cooling water temperature is decided to be 80°C and 25°C while the chill water temperature proposed is 14°C. The optimum cycle time is decided to be 820 seconds. The temperature profile of different components in the proposed adsorption cooling system is produced. The COP and SCC of the proposed adsorption cooling system as the values are adopted in the simulation is 0.5481 and 15.856 kilowatts.